Identifikasi Konsep Merdeka Belajar Guru Smk Di Kota/Kabupaten Kediri Sebagai Bahan Refleksi Dalam Pelaksanaan Pembelajaran Kurikulum Merdeka: Identification of the Concept of Merdeka Belajar for Smk Teachers in Kediri City / District As Reflection Material in the Implementation of Independent Curriculum Learning - Widiastuti, Sussi; Tarigan, Ima Pinensi Br; Cinantya, Ixsora Gupita (Efektor, 2023)
Abstract Merdeka Belajar is a policy that aims to provide schools flexibility in planning, implementing and evaluating educational programs, with reference the principles of Merdeka Belajar policy set by the central government. The concept of Merdeka Belajar demands a change in the teacher's paradigm. This article discusses the results of Merdeka Belajar identification owned by teachers as material for reflection in Kurikulum Merdeka implementation. Concepts identification include: 1). moving level as a diagnosis of change drivers, 2). strategy and scope of learning, 3). Merdeka Belajar, 4). and leader style. This research method is survey research with 1,939 teachers as respondents at Kota/Kabupaten Kediri. Data collection was carried out by implementing an internet-based survey. The survey results show that the majority of teachers (45.1%) are at the mobile level 2, namely having an agenda to move, but requiring consistency. Teacher's understanding of strategy and learning 72.4%. The lowest implementation of Merdeka Belajar is learning reflection (81.2%). The "guard" leadership style (56.5%) is the majority leadership style. Information about the concept of Merdeka Belajar teachers at Kota/Kabupaten Kediri will be used as material for reflection as a growth mindset in the implementation of Kurikulum Merdeka.